2014
DOI: 10.5505/tjtes.2015.64505
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of power Doppler sonography in acute cholecystitis to predict intraoperative findings: Prospective clinical study

Abstract: BACKGROUND:This study aimed to evaluate the diagnostic value of gray-scale and power Doppler sonography for acute cholecystitis and show a correlation between sonographic and intraoperative findings, quantitively. METHODS:Forty chronic and forty acute cholecystitis patients were examined. Early laparoscopic cholecystectomy was performed for acute cholecystitis. Demographic characteristics, sonographic findings, and adhesion scores were analyzed. Data were collected prospectively (clinicaltrials.gov: NCT0215694… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…A study of the use of color Doppler sonography in acute cholecystitis found that although it was useful for the diagnosis of gallbladder adhesions, it was not predictive of the degree of surgical difficulty . In our search of the literature relevant to the color Doppler sonography, we were unable to identify any articles concerning the diagnosis of acute cholecystitis.…”
Section: Introductionmentioning
confidence: 91%
“…A study of the use of color Doppler sonography in acute cholecystitis found that although it was useful for the diagnosis of gallbladder adhesions, it was not predictive of the degree of surgical difficulty . In our search of the literature relevant to the color Doppler sonography, we were unable to identify any articles concerning the diagnosis of acute cholecystitis.…”
Section: Introductionmentioning
confidence: 91%
“…Yamashita et al suggested that gallbladder wall flow positively correlates with the degree of inflammation in the acute setting, proposing this method for monitoring treatment success (17). Cetinkunar et al evaluated gallbladder wall vascularity using Power Doppler, and came to the conclusion that increased vascularity correlates with the presence of adhesions, but not with operation difficulty (5). More recently Loehfelm et al proposed that a peak systolic hepatic artery velocity of more than 100 cm/sec represents a significant aid in diagnosing acute cholecystitis (7).…”
Section: Resultsmentioning
confidence: 99%
“…Patients with equivocal findings were excluded from the analysis, in an attempt to counterbalance the non-availability of pathological confirmation of acute cholecystitis. Exclusion criteria also included the following comorbidities: choledocholithiasis (due to the fact that concurrent cholangitis may affect hepatic artery velocity, thus acting as a confounding factor); pancreatitis, congestive heart failure, liver cirrhosis, renal failure, hypoalbuminemia, and hepatitis (due to the fact that these conditions are known to cause gallbladder wall thickening thus being potential confounders) (5,6,9); arteriosclerosis, decreased intravascular volume due to severe dehydration, and hyperdynamic circulatory state due to high fever (because PI measurement is greatly affected by the condition of the arteries, the circulating blood volume and a hyperdynamic circulation state).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation